Statistical shape modeling of the pelvic floor to evaluate women with obstructed defecation symptoms. Issue 2 (25th January 2021) - Routzong, Megan R.; Rostaminia, Ghazaleh; Bowen, Shaniel T.; Goldberg, Roger P.; Abramowitch, Steven D.
Abstract: Obstructed defecation (OD) is common and may be related to compromised pelvic floor integrity. Magnetic resonance (MR) defecography and statistical shape modeling were used to define pelvic floor shape variations, hypothesizing that State (rest vs peak evacuation) and Group (control vs case) would significantly influence shape. 16 women underwent MR defecography (9 cases vs 7 controls). Midsagittal, 2D pelvic floors were segmented and aligned by corresponding points. Principal component scores were compared using a Two-Way Mixed MANOVA. Three modes described differences between State (p < 0.001) and Group (p = 0.023). The pelvic floor shape differed significantly between women with and without OD and during evacuation.